Fuzzy Decision Support System for Financial Planning and Management (Informatica, 2024)
In a rapidly changing business environment, enterprises are facing increasingly complex and uncertain financial management challenges. Traditional financial management methods are becoming inadequate, especially in dealing with massive amounts of data, forecasting market dynamics, and formulating flexible response strategies. Especially in today's globalization, market competition and frequent economic fluctuations, enterprises need a more intelligent and dynamic decision support tool to assist financial management, in order to achieve optimal allocation of resources, reduce risks, and improve decision-making efficiency and quality. This paper introduces the design, development and evaluation of fuzzy decision support system (FDSS) for Blue Ocean Technology Co., Ltd. FDSS is based on a microservices architecture that combines modularity, scalability and intelligence to improve flexibility and efficiency in financial management. The core of the system includes fuzzy logic algorithm to deal with fuzziness and uncertainty, multilayer perceptron (MLP) neural network to realize data prediction, and genetic algorithm to optimize decision rules and model parameters. The DOE details the technical architecture, data integration and processing processes, and model evaluation methodology. Empirical studies show that FDSS significantly improves budget management, risk warning, investment decision-making efficiency and financial health, which is manifested in the reduction of budget overspending rate, early warning time, shortened decision-making cycle and improved financial health index.